Superhydrophobic Pd@CeO2/Al2O3 catalyst coating for hydrogen mitigation systems in nuclear power plants. (13th August 2019) - Yan, Peijian; Xiao, Junyin; Yu, Wei; Zhao, Chen; Yu, Xinhai; Zhao, Shuangliang; Zhou, Shenghu; Tu, Shan-Tung
Abstract: Passive autocatalytic recombination (PAR) was employed as an effective hydrogen mitigation system for nuclear power plants. Despite the great progress achieved in catalysts for PAR, few reports could be found on PAR catalysts, which exhibit strong resistance to poisoning by iodine compounds and the detrimental effect of water, as well as good anti-sintering properties. In this study, a superhydrophobic Pd@CeO2 /Al2 O3 catalyst coating was prepared through a self-assembly method and the grafting of 1H, 1H, 2H, 2H-perfluorooctyltriethoxysilane. The superhydrophobicity of the catalyst coating effectively alleviated water poisoning. The ceria shell of Pd@CeO2 /Al2 O3 served as a protective layer against poisoning by iodine compounds because it was difficult for iodine vapor to access the catalyst core of the Pd nanoparticles when the shell pore diameter was below 1.2 nm. Given the interface effect between palladium and ceria, the CeO2 shells also served as an effective barrier to prevent the Pd nanoparticles from aggregating at high temperatures. The superhydrophobic Pd@CeO2 /Al2 O3 coating showed excellent potential for the mitigation of hydrogen containing various poisons during a nuclear accident. Graphical abstract: Image 1 Highlights: Superhydrophobic Pd@CeO2 /Al2 O3 was prepared through self-assembly and grafting methods. Ceria shell of Pd@CeO2 /Al2 O3 served as a protective layer from poisoning of iodine compounds. Ceria shell prevented Pd nanoparticles from aggregating at high temperatures.